2012
DOI: 10.1140/epjst/e2012-01619-x
|View full text |Cite
|
Sign up to set email alerts
|

Multiwavelength anomalous diffraction and diffraction anomalous fine structure to study composition and strain of semiconductor nanostructures

Abstract: Abstract. The aim of this paper is to illustrate the use of MultiWavelength Anomalous Diffraction (MAD) and Diffraction Anomalous Fine Structure (DAFS) spectroscopy for the study of structural properties of semiconductor nanostructures. We give a brief introduction on the basic principles of these techniques providing a detailed bibliography. Then we focus on the data reduction and analysis and we give specific examples of their application on three different kinds of semiconductor nanostructures: Ge/Si nanois… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 92 publications
0
21
0
1
Order By: Relevance
“…Also worthy of mention are anomalous X-ray scattering methods, such as multiwavelength anomalous diffraction (MAD) and diffraction anomalous fine structure (DAFS) [12]. Methods using nanobeam X-ray diffraction (NBXD) [13] have been intensively developed in recent years.…”
Section: Introduction Methods Of Research On Structures With Quantummentioning
confidence: 99%
See 1 more Smart Citation
“…Also worthy of mention are anomalous X-ray scattering methods, such as multiwavelength anomalous diffraction (MAD) and diffraction anomalous fine structure (DAFS) [12]. Methods using nanobeam X-ray diffraction (NBXD) [13] have been intensively developed in recent years.…”
Section: Introduction Methods Of Research On Structures With Quantummentioning
confidence: 99%
“…whereẽ s rr n n is given by (12). The diffuse scattering amplitude in (10) can be represented as the sum of two terms,…”
Section: Diffuse Scattering From Epitaxial Structures With Quantum Domentioning
confidence: 99%
“…ÅAEÇẽ s rr n n ÊÂAEÂÈÕÔâ ÔÑÑÕÐÑÛÇÐËÇÏ (12). ¡ÏÒÎËÕÖAEÖ AEË××ÖÊÐÑÅÑ ÓÂÔÔÇâÐËâ Ä (10) ÒÓÇAEÔÕÂÄËÏ Ä ÄËAEÇ ÔÖÏÏÞ AEÄÖØ ÔÎÂÅÂÇÏÞØ: …”
Section: ³õâõëôõëúçôíââ õçñóëâ óçðõåçðñäôíñì Aeë×óâíùëëunclassified
“…Thus, the local atomic configuration and chemical state can be determined around a certain element at a particular crystallographic site of a unit cell and also in a particular crystalline phase of a sample. Pioneering DAFS studies, including theoretical introductions, have been reported (Renevier et al, 1997;Cross et al, 1998;Meyer et al, 1999;Proietti et al, 1999;Lee et al, 2006;Joly et al, 2008) and reviewed (Sorensen et al, 1994;Favre-Nicolin et al, 2012;Palancher et al, 2012;Zschornak et al, 2014). However, there have been few reports on the application of DAFS to practical materials, which often require specific types of investigations (such as a time-series variation associated with the durability and degradation of product performances), presumably because of the two scientific challenges discussed below.…”
Section: Introductionmentioning
confidence: 99%
“…Stragier et al (1992) divided a DAFS spectrum into smooth and oscillating parts and extracted spectrum oscillations by fitting the smooth part with a theoretically calculated profile. This calculation method has subsequently inspired analyses of data for extended diffraction anomalous fine structure (EDAFS), which is analogous to extended X-ray absorption fine structure (EXAFS) (Favre-Nicolin et al, 2012), but the method is not applicable to analyses of data for diffraction anomalous near-edge structure (DANES), which corresponds to X-ray absorption near-edge structure. Pickering et al (1993) and Vacínová et al (1995) proposed the iterative-fitting method, by which an entire DAFS spectrum is fitted using presumed f 0 ðEÞ or f 00 ðEÞ values.…”
Section: Introductionmentioning
confidence: 99%